Innovations in practice: an objective measure of attention, impulsivity and activity reduces time to confirm attention deficit/hyperactivity disorder diagnosis in children: a completed audit cycle - Hall, Charlotte L.; Selby, Kim; Guo, Boliang; Valentine, Althea Z.; Walker, Gemma M.; Hollis, Chris (Wiley, 2016)
Background